2006
DOI: 10.1111/j.1526-4610.2006.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Sodium Increases in Migraine

Abstract: Background.-Pharmaceuticals with calcium-or sodium-channel-blocking activity have proven useful for migraine prophylaxis, and calcium channel, sodium transporter, and sodium channel gene mutations have been found in familial hemiplegic migraine. However, it is not known whether calcium or sodium homeostasis is altered in migraine.Objective.-To compare levels of sodium, calcium, potassium, and magnesium in cerebrospinal fluid (CSF) and blood plasma between migraineurs and controls.Methods.-We recruited 20 migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 33 publications
0
68
0
Order By: Relevance
“…This upper limit was similar to the upper reference levels of 3.6 -4.1 mmol/L in the CSF of controls described by others. 2,3 Is the ionic profile normal in the apparently non-damaged brain?…”
Section: The Ionic Profile Of the Normal Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…This upper limit was similar to the upper reference levels of 3.6 -4.1 mmol/L in the CSF of controls described by others. 2,3 Is the ionic profile normal in the apparently non-damaged brain?…”
Section: The Ionic Profile Of the Normal Brainmentioning
confidence: 99%
“…Under steady state, the intracellular concentration of potassium ([K + ] i ) in the CNS is typically around 145 mmol/L, and the extracellular potassium concentration ([K + ] o ) is ~3 mmol/L. [1][2][3] Transmembrane sodium gradients have the opposite orientation, and the extracellular concentration of sodium ([Na + ] o ) is much higher that its intracellular concentration ([Na + ] i ). The ATP-dependent Na + /K + -pump of intact brain cells maintains a concentration gradient between the intracellular and extracellular compartments of approximately 1:10.…”
Section: Introductionmentioning
confidence: 99%
“…29 We suggest that, during increased NKAT activity, the decrease in [K + ]e/csf has been minimized by the strong glial regulation system for [K + ]. 45 The magnitude of the NKAT role in the brain 42,43 suggests that its increased activity is the most likely cause of the increased [Na + ]csf and [Na + ]e in migraine, though further studies of [Na + ]e and [Na + ]csf are required.…”
Section: Increased Cec Nkat Activity Is the Likely Mechanism For Incrmentioning
confidence: 88%
“…29 [Na + ]csf rose significantly during the peak of migraine compared with the non-headache state of migraineurs and controls. This increase is found only in the cerebrospinal fluid (CSF) and not the plasma samples of migraineurs, which argues for a brain source and against a systemic origin.…”
mentioning
confidence: 90%
“…et.al. [79] have studied cerebrospinal fluid sodium increate in migraine and found that modestly elevated extracellular Na(+) in MH(+) may cause the neural changes that underline clinical features of migraine.…”
Section: O P Y R I G H T © S O C I E T Y F O R S C I E N C E a N D mentioning
confidence: 99%